Strengthening local enterprise: A development plan based on the promotion and distribution practices of OTOP beneficiaries in Nueva Ecija, Philippines - Murillo, Lady Anne (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to examine the promotion and distribution strategies employed by One Town One Product (OTOP) micro, small, and medium enterprises (MSMEs) in Nueva Ecija, Philippines. It sought to identify the challenges these enterprises face and provide data-driven inputs for a development plan aimed at enhancing their market competitiveness and long-term sustainability. A descriptive-quantitative research design was employed. Data were collected using a validated survey instrument administered to OTOP beneficiaries throughout the province. The analysis covered key promotional strategies including advertising, personal selling, public relations, and sales promotion and core distribution components including customer service, order processing, materials handling, inventory management, delivery, and product return protocols. Results indicated that OTOP MSMEs demonstrate strong practices in branding, customer service, and public relations. However, gaps were observed in areas such as digital tool utilization, formal inventory and return systems, and comprehensive strategic marketing planning. Specific operational challenges included limited digital literacy, underutilization of courier services, and low formalization in handling customer returns and feedback. The study concludes that while OTOP MSMEs have established foundational strengths in traditional promotional and distribution strategies, there is a pressing need to enhance digital capabilities, formalize operational systems, and adopt structured marketing approaches. A development plan is proposed to address these gaps through targeted interventions. The findings offer actionable insights for MSMEs, local government units, and development agencies in crafting responsive support programs. Emphasis should be placed on digital training, capacity-building in strategic marketing, investment in inventory and order management tools, and expansion of promotional platforms. These efforts can contribute to strengthening local enterprises and fostering inclusive and sustainable economic growth at the community level.